(untitled) (Global Journal of Management and Business Research, 2015)
The term "supply chain management" has become a popular buzzword, probably first used by consultants in the late 1980s & then analyzed by the academic community in the 1990s. if one wants a simple definition, supply chain management links all the supply interacting organizations in an integrated two-way communication system to manage high quality inventory in the most effective & efficient manner. The supply chain management reflects those actions & values responsible for the continuous improvement of the design, development & management processes of an organization’s supply system, with the objective of improving its profitability & ensuring its survival, as well as the profitability & survival of its customers & suppliers.